THE EFFECT OF PERCEIVED USEFULNESS AND PERCEIVED EASE OF USE ON ONLINE BUYING INTEREST IS THROUGH THE ATTITUDE OF USING SOCIAL MEDIA (International Conference of Graduate School on Sustainability (ICGSS), 2020)
The development of information technology has penetrated various aspects of social life, including the pattern or lifestyle of the community in buying and selling activities. With the very rapid development of technology today plays an important role in fulfilling all the needs of society. Currently, on average, all levels of society use internet media every time they do something, especially during the Covid 19 period, where like it or not and like it or not, people are required to use something online, including in buying and selling or trading transactions. Electronic commerce or e-commerce is an e-lifestyle trading system today by enabling buying and selling transactions to be made online. This research is used to see from the Technological Acceptance Model (TAM) theory with every activity related to technology or information systems used to find out the easy benefits and ease of use of the technology used and associated with the attitude of using social media towards online buying interest. The population in this study are all people who use or have purchased goods transactions online, the sample in this study amounted to 147 respondents. Data analysis using: Validity Test, Reliability Test, path analysis. The results of the analysis show that the perceived benefits and ease of use have a significant effect on the attitude of using social media and buying interest online. However, when viewed from the indirect effect, the perceived benefits and ease of use do not have a significant effect on online buying interest through the attitude of using social media.   Keywords : Tachnology Aceptance perceived benefits and ease of use, Buying Interest Online, Satisfaction